Next generation multi epitope based peptide vaccine against Marburg Virus disease combined with molecular docking studies - Mujahed I. Mustafa; Shaza W. Shantier (Informatics in Medicine Unlocked, 2022)
Background: Marburg virus disease (MVD) is a hemorrhagic fever that can kill up to 88% of people. It is transmitted through skin contact or mucous membrane in the eyes, nose, or mouth with blood or body fluids such as urine, saliva, sweat, feces, and by object contaminated with body fluids. Despite these facts, no approved vaccine for the eradication of Marburg virus infections has been developed. Methods: This study described a multi epitope-based peptide vaccine against Marburg virus viral protein 35, using several immunoinformatics tools combined with molecular docking and dynamic simulation studies. Results: Utilizing Vaxijen 2.0 server, the V35 protein revealed to be antigenic with a score of 0.4316. Prediction of the T-cell and B-cell epitopes was then conducted. RTFDAFLGV epitope was found to be the most promising one with binding affinity to the highest numbers of MHC I alleles, a positive score in the Class I immunogenicity study and non-allergen. These results were further confirmed by the good interaction of RTFDAFLGV to the groove of HLA-A*02:01 with binding energy of −8.1 kcal/mol. Finally, the vaccine was cloned in silico to ensure its validity and efficiency of expression. Conclusion: To ensure its safety and immunogenic profile, in-vitro and in-vivo bioassays are recommended to confirm these findings.